Vitamin A levels for growing-finishing pigs - Koch, B.A. (Kansas Agricultural Experiment Station, 2011)
Vitamin A supplementation recommendations vary considerably from station to station. Most research indicates that supplementation recommendations are generally much higher than actually necessary. This study was designed to determine performance response to low-level vitamin A supplementation of an otherwise adequate diet.
Keywords: Swine; Vitamin A; Backfat